Determination of Radical–Radical Distances in Light‐Active Proteins and Their Implication for Biological Magnetoreception. Issue 29 (19th June 2017) - Nohr, Daniel; Paulus, Bernd; Rodriguez, Ryan; Okafuji, Asako; Bittl, Robert; Schleicher, Erik; Weber, Stefan
Abstract: Light‐generated short‐lived radial pairs have been suggested to play pivotal roles in cryptochromes and photolyases. Cryptochromes are very probably involved in magnetic compass sensing in migratory birds and the magnetic‐field‐dependent behavior of insects. We examined photo‐generated transient states in the cryptochrome of Drosophila melanogaster and in the structurally related DNA‐repair enzyme Escherichia coli DNA photolyase. Using pulsed EPR spectroscopy, the exchange and dipolar contributions to the electron spin–spin interaction were determined in a straightforward and direct way. With these parameters, radical‐pair partners may be identified and the magnetoreceptor efficiency of cryptochromes can be evaluated. We present compelling evidence for an extended electron‐transfer cascade in the Drosophila cryptochrome, and identified W394 as a key residue for flavin photoreduction and formation of a spin‐correlated radical pair with a sufficient lifetime for high‐sensitivity magnetic‐field sensing. Abstract : Short‐lived spin‐correlated radical pairs are essential for the kind of magnetic compass that is believed to be used by migratory birds and insects to perceive direction. Such transient states were studied by pulsed EPR spectroscopy, and the distance‐dependent magnetic couplings between the unpaired spins were characterized.